GAMBARAN KETEPATAN PENGODEAN PENYEBAB KEMATIAN PADA SERTIFIKAT MEDIS PENYEBAB KEMATIAN KASUS PERINATAL DI RSIA TIARA CIKUPA - Octa Rina Sari; Laela Indawati; Noor Yulia; Lily Widjaja (Nusantara Hasana Journal, 2023)
The basic cause of death is used as an evaluation of a health service, knowing the general health status, reporting mortality and prevention of deadly diseases and preparing for medical needs in the future. The purpose of this research is to know the description of the accuracy of the coding accuracy of the cause of death on the perinatal case death certificate at RSIA Tiara. The research method used in this research is a descriptive mix method where a mix of quantitative and qualitative is by describing and explaining the accuracy of the UCoD coding on medical certificates causing death in perinatal cases. The population in this study were all medical records of babies who died in 2020, 2021 and 2022, totaling 32 medical records. The sample used in this study was a saturated sample where all populations were sampled, namely 32 medical records. The results of the presentation of the accuracy of the coding on the medical certification cause of death were as much as 69% while those that were not correct were as many as 31%. It is preferable to code all diagnoses in the prenatal case death certificate using the guideline and rules P1,P2,P3,P4 to give the correct code. Factors causing inaccuracy in codification of the underlying cause of death on the death certificate, the doctor's writing on the infant's medical resume in the final diagnosis section using cursive letters creates obstacles for the coding officer in determining the correct code. There is no special SPO for coding prenatal cases. Lack of human resources with a background in medical records.